Annual Subsistence Cycle of the Chepangs in mid-hills of Nepal: An Integration of Farming and Gathering - Maharjan, Keshav Lall; Piya, Luni; Joshi, Niraj Prakash (Himalayan Journal of Sociology and Anthropology, 2011)
No Abstract DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4671 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 105-133